Static and fatigue debond resistance between the composite facesheet and Al cores under Mode-1 in sandwich beams - Selvam, Vignesh (2022)
The debonding toughness between unidirectional glass fiber reinforced polymer face sheets and cellularic cores of sandwich structures is experimentally measured under static and fatigue loading conditions. The effect of various core geometries, such as regular honeycomb and closed-cell foams of two relative densities on the adhesive interfacial toughness is explored using the single cantilever beam (SCB) testing method. The steady-state crack growth measurements are used to plot the Paris curves. The uniformity of adhesive filleting and the crack path was found to affect the interfacial toughness. The static Mode-1 interfacial toughness of high-density foam cores was witnessed to be maximal, followed by low-density honeycomb, high-density honeycomb, and low-density foam core. Similarly, the fatigue behavior of the low-density honeycomb core has the lowest crack growth rates compared to the other samples, primarily due to uniform adhesive filleting.